WEDDINGS PRAYERS IN THE TRADITION OF BERDIMBAR BATHING IN COAL MELAYU TRADITIONAL : ANTROPOLINGUISTIK - siti nurhaliza sihombing; Dardanila Dardanila (Edukasi Kultura, 2024)
This thesis aims to prove the meaning and value of Anthropolinguistic culture in the Mandi Berdimbar tradition at the Batubara Malayu traditional wedding ceremony. Furthermore, this study aims to provide an update on the overall topic of Anthropolinguistic studies in traditional marriage traditions. The research object is language. The focus of this research is on the meaning of the expression of prayer or called Ketubah Nikah and focuses on the cultural values contained therein. This study uses a qualitative descriptive method by describing the meanings and values of Anthropolinguistic culture based on the theory of meaning and values of Anthropolinguistic culture. The results of this study indicate that in the Mandi Berdimbar tradition it contains the meaning of advising, the meaning of hope, and the equalization (comparison) of each Ketubah Nikah which is pronounced during the traditional procession. Cultural values are also found in this traditional tradition, including religious cultural values, cultural values of harmony, cultural commitment values, politeness cultural values, health cultural values, mutual cooperation cultural values, cultural values of gender management.